Stability Analysis in a Grid-interactive Residential Nanogrid Using Markov Chains - Dahiru A.T.; Tan C.W.; Bukar A.L.; Lau K.Y.; Toh C.L.; Salisu S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Decision trees; Economic and social effects; Housing; Intelligent systems; Matrix algebra; Renewable energy resources; Statistical mechanics; Stochastic systems; Systems analysis; Markovian; matrix; MonteCarlo methods; Nanogrid sizing; Nanogrids; Probabilistic information; State transitions; Steady state; Steady-state transition; Transition probabilities; Monte Carlo methods